The impact of a malignant diagnosis on the pattern and outcome of readmission after liver and pancreatic surgery: An analysis of the nationwide readmissions database. Issue 8 (29th June 2018) - Bagante, Fabio; Beal, Eliza W.; Merath, Katiuscha; Paredes, Anghela; Chakedis, Jeffery; Olsen, Griffin; Akgül, Ozgür; Idrees, Jay; Chen, Quinu; Pawlik, Timothy M.
Abstract : Background and Objectives: Reducing readmissions is an important quality improvement metric. We sought to investigate patterns of 90‐day readmission after hepato‐pancreatic (HP) procedures. Methods: The Nationwide Readmissions Database (NRD) was used to identify patients undergoing HP procedures between 2010 and 2014. Patients were stratified according to benign versus malignant HP diagnoses and as index (same hospital as operation) versus non‐index (different hospital) readmissions. Results: Among the 41 059 patients who underwent HP procedures, 26 563 (65%) underwent a liver resection while 14 496 (35%) pancreatic resection. Among all patients, 11 902 (29%) had a benign diagnosis versus 29 157 (71%) who had a cancer diagnosis. Overall 90‐day readmission was 22% ( n = 8 998) with a slight increase in readmissions among patients with a malignant ( n = 6 655;23%) versus benign ( n = 2 343;20%) diagnosis ( P < 0.001). Readmission to an index hospital was more common ( n = 7 316 81%) versus a non‐index hospital ( n = 1 682 19%). Non‐index hospital readmissions were more frequent among patients with malignant HP diagnoses (OR, 1.41; P = 0.001). Conclusions: Up to one in four patients were readmitted after HP surgery. Late readmission was more common among patients with a cancer‐diagnosis. While most readmissions occurred at the index hospital, 19% of all readmissions occurred at a non‐index hospital and were more frequent among patients with malignant diagnoses.